Assessment of digital panoramic radiography's diagnostic value in angular bony lesions with 5 mm or deeper pocket depth in mandibular molars - Bardia Vadiati Saberi; Somayeh Nemati; Meisam Malekzadeh; Afrooz Javanmard (Wolters Kluwer Medknow Publications, 2017)
Background: Assessment of alveolar bone level in periodontitis is very important in determining prognosis and treatment plan. Panoramic radiography is a diagnostic tool used to screen patients. The aim of the present study was to assess the diagnostic value of digital panoramic radiography in angular bony defects with 5 mm or deeper pocket depth in mandibular molars. Materials and Methods: In this cross-sectional study, ninety angular bony defects in mandibular molars teeth with 5 mm or deeper pocket depth were selected in sixty patients with the diagnosis of chronic periodontitis. Before surgery, bone probing was performed. During the surgery, the vertical distance from cementoenamel junction to the most apical part of bony defect was measured using a Williams probe and this measurements were employed as gold standard. This distance was measured on the panoramic radiographs by a Digital Calliper and Digital Ruler. All data were compare dusing independent samples t-test and Pearson's correlation coefficient. Results: No significant difference was found between the results of bone probing and intra-surgical measurements (P = 0.377). The mean defect depth determined by Digital Caliper and Digital Ruler on panoramic radiographs was significantly less than surgical measurements (P < 0.001). The correlation between bone probing and surgical measurements in determining the defect depth was strong (r = 0.98, P < 0.001). Radiographic measurements made by Digital Ruler (r = 0.86), comparing to Digital Caliper (r = 0.79), showed a higher degree of correlation with surgical measurements. Conclusion: Based on this study, bone probing is a reliable method in vertical alveolar bone defect measurements. While the information obtained from digital panoramic radiographs should be used with caution and the ability of digital panoramic radiography in the determination of defect depth is limited.